De educador a administrador; de administrador a educador: uma narrativa interdisciplinar como possibilidade de currículo para o educador administrador escolar contemporâneo - Fernandes, Peterson José Cruz (2018)
Given the complex context which challenges the contemporary private schools and, therefore, its own administration, this research – action – formation is aimed at answering the following questions: Who is the administrator of a school today? An educator or a manager? By making use of an interdisciplinary account of the researcher’s life story, the study seeks to systematize elements that could criticise a reality which offers risks to the identity of the school which, on its turn, has compromised its mission; and at the same time, seeks to present possibilities of ways and actions towards the building up of the curriculum of the professional that administrates schools today. From this moviment, it has become possible to develop a series of theoretical and practical inputs in order to build a curriculum abounding potentials to overcome existing dichotomies inside a school these days, particularly the Administration/Educational one, as it has been guided by the Interdisciplinarity, which enables to address the complexity of a school in a more suitable way, since it is integrated and, thus, integrator. This curriculum is organized upon three bases: Strong theoretical and practical formation; interdisciplinary experience and self – awareness. It enables the qualification of a school educator – administrator (answer to the initial questions) competent enough to articulate a wide range of contribution in the approach of school and educational contemporary elements. Through this journey, this professional has the opportunity to develop his own skills: consistency, humbleness, detachment, respect, waiting ability and capability to conceive a Phylosophy of School Administration